Σχεδιασμός διεπαφής προγραμματισμού εφαρμογών (API) για την υλοποίηση γεωδαιτικών υπηρεσιών μετασχηματισμού συντεταγμένων - Καλογήρου, Βασίλειος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Coordinate Reference Systems and coordinate transformation processes are key subjects with which a Surveyor Engineer is involved. This thesis studies the theoretical background of these subjects and indicates the importance of carrying out these operations through a software application. Since such an application has not been formed in Cyprus, the aim of this thesis is the development of a library that enables coordinate transformations of Cyprus spatial infrastructure as well as the design of an Application Programming to support this library with the prospect of being transformed into an integrated geodetic service.
Keywords: Geodesy; Geodetic reference systems; Coordinate systems; Projections; Coordinate transformation; Γεωδαισία; Γεωδαιτικά συστήματα αναφοράς; Συστήματα συντεταγμένων; Προβολές; Μετασχηματισμός συντεταγμένων